PENGEMBANGAN METODE EVALUASI KEKUATAN PROFIL BAJA PERSEGI MENGGUNAKAN PEMANFAATAN GABUNGAN TEORI MEKANISME PLASTIS DAN ELASTIS = DEVELOPMENT OF STRENGTH EVALUATION METHOD OF A SQUARE HOLLOW STEEL SECTION USING THE APPLIACATION OF COMBINED THEORIES OF PLASTIC MECHANISMS AND ELASTIC APPROACH - M. Kadir, Andi; Priadi, Dedi; S. Siradj, Eddy; S, Harkali (Majalah Ilmiah Pengkajian Industri, 2015)
AbstractDesign analysis method developed in this study did not use a safety factor that can be used for the design of steel structures that are capable of supporting heavy working load with the weight as light as possible in order to obtain an effective and efficient structure in terms of technical and economic. In this research program, a method of cut-off strength is used as a basis of predicting the strength of a square hollow steel section affected by the interaction of concentrated-compressive load and bending moment. The method cut-off strength is illustrated in the form of two plastic and elastic curves of loaddeflection, where the value of load at an intersection of these curves is assumed to be the theoretical strength of the steel section with respect to the interaction of concentrated-compressive load and bending moment. The plastic curve is established according to a load-deflection equation that is developed through the analysis of energy equilibrium on the plastic failure mechanisms model of the steel section. Meanwhile, the elastic one is established according to another load-deflection curve that is developed through the analysis of non linear elastic concept of the steel structure. This analytical method is implemented by using computer software. In order to measure the accuracy of the design of this analytical model developed in this program, its predicted results are verified using actual strength data obtained from a number of tests on the square hollow steel sections subjected to the interaction of concentrated-compressive load and bending moment to failure. Verification results indicate that the ratio of the analytical-predicted data and experimental one is still scattered within tolerable limits of ± 20 %. AbsrakMetode analisis disain yang dikembangkan didalam penelitian ini tidak menggunakan faktor keamanan sehingga dapat digunakan untuk mendisain struktur baja yang mampu mendukung beban kerja dengan berat yang seringanmungkin sehingga diperoleh struktur yang efektif dan efisien dari segi teknis dan ekonomi. Dalam penelitian ini, suatu metode cut-off strength digunakan sebagai dasar untuk memprediksi kekuatan profil baja ringan berpenampang persegi (SHS) akibat interaksi beban tekan memusat dan momen lentur. Metode cut-off strength diilustrasikan dalam bentuk dua kurva beban-defleksi plastis dan elastis, dimana nilai beban diperpotongan kedua kurva tersebut diasumsikan sebagai kekuatan teoritis profil baja SHS terhadap interaksi tekan memusat dan momen lentur. Kurva plastis dibentuk berdasarkan persamaan beban-defleksi yang dikembangkan melalui analisis kesetimbangan energi model mekanismekerusakan plastis profil baja SHS. Sementara itu, kurva elastis dibentuk berdasarkan persamaan beban-defleksi yang dikembangkan melalui analisis non-linear elastic profil baja SHS dengan mempertimbangkan efek local buckling pada penampang profil yang tertekan. Metode analisis ini diimplementasikan dengan menggunakan perangkat lunak (software) komputer. Untuk mengukur ketelitian model analisis disain yang dikembangkan dalam penelitian ini, hasilprediksi kekuatan profil baja SHS diverifikasi menggunakan data kekuatan aktual yang dihasilkan melalui pengujian sejumlah profil baja SHS akibat interaksi beban tekan memusat dan momen lentur sampai rusak. Hasil verifikasi menunjukkan bahwa rasio data prediksi analitis dan eksperimental masihtersebar dalam batas-batas toleransi yang umum digunakan yaitu ± 20 %.